Relation between Hematological and Biochemical Parameters per Days of Symptoms in Hospitalized Patients with flu-like syndrome and COVID-19 (Research, Society and Development, 2022)
Beside the acute respiratory syndrome caused by COVID-19, the exacerbated inflammatory process leads to systemic coagulation disorders, acute cardiovascular disorders, acute renal failure, metabolic changes and other clinical manifestations, increasing the mortality of patients with severe forms of the disease. The development of effective vaccines and drugs for the adequate treatment of severe forms of the disease has become a priority for the scientific and medical community. Likewise, the discovery of possible predictors for the early identification of severe cases with a high risk of death are constantly being sought. Laboratory tests, such as blood count, coagulation tests, hormonal and biochemical tests, are performed on a daily basis in the hospital environment and have proved to be very useful in the search for these indicators. In our study, we evaluated the laboratory tests of 398 positive and negative patients for COVID-19 admitted to hospitals in Uberaba, from the Macroregion of Triângulo Sul, state of Minas Gerais, with a population of 800,000 inhabitants. In our results, it was observed that the patients who died presented anemia, neutrophilic leukocytosis, increased CRP, urea and creatinine from the 5th, 6th day of symptoms, and with lymphopenia on the 1st day. In blood gas analysis, pH, SaO2 and PO2 were reduced since the 1st day of symptoms in patients who died, and the pH remained reduced until the clinical outcome. Changes were also found in the dosage of LDH, aPTT, albumin and electrolytes. Given these results, laboratory tests can be useful as predictive signs of severity in the early days of symptoms.